Testicular pigmentation in Physalaemus nattereri (Steindachner) (Amphibia, Anura) with anatomical observations on the extracutaneous pigmentary system - [Anonymous] (Sociedade Brasileira De Zoologia, Univ Federal Parana, 2005)
The testes in the anurans are paired ovoid organs constituted by seminiferous structures surrounded by the fibrous connective tissue, commonly unprovided ofpigments. This study tried to analyze the morphological characteristics of rare and conspicuous pigment-containing cells and their relationship with other structures. The pigment cells are variously and indistinctly also termed Kuppfer cells in the liver, pigment cells, extracutaneous pigment cells, pigmented macrophages, melanomacrophages, melanophage, melanophores and melanocytes in the liver, spleen and kidney and other visceral structures of exothermic vertebrates. Ten male samples of Physalaemus nattereri (Steindachner, 1863) (Leptodactylidae) were used. After macroscopic analyses, the testicular fragments weresubmitted to the histological routine, fixed with karnovisky, embedded Historesin and coloration with Haematoxylin/Eosin. A rare peculiarity was the presence of numerous pigment-containing cells (melanocytes) randomly distributed in the albuginea tunic and testicular interstitium, giving the testes a dark brown coloration. This unusual characteristic has been rarely described and in other lower vertebrates, the pigment cells can be found in different organs, constituting an extracutaneous pigmentary system of unknown function. Further, it was identified a conspicuous variation, as to presence and distribution pattern due to possible species-specific aspects. However, histologically there is no difference in the germ epithelium arrangement. Between the seminiferous locules, there is an inter-locular tissue composed by Leydig interstitial cells, fibroblasts, efferent ductules, melanocytes and blood vessels. This inter-locular tissue is relatively scarce, presenting melanocytes in all specimens analyzed intimate associated with blood vessels. They are irregular cells with numerous melanosomes and long cytoplasmic processes.